Dynamic game theoretic models in predicting responses of competitors in oligopolistic markets - Shahrjerdi, Reza (2014)
Differential games theory can be considered as new theory in economic analysis for the oligopolistic market competition. The game theory is used to find the importance interaction between firms. Therefore, in this thesis the author attempted to assess the competition between firms in the oligopolistic market. Previous game theory model is focused on static and monopolistic market. However, the actual market condition cannot be considered as static. Therefore, there is a need to represent this static condition of the previous model to dynamics model. Currently there are few models represent the dynamic market conditions, however it is failed to incorporate continuous-time condition in oligopolistic markets with related to price and quantity issues. In dynamic market model, strategies of the games theory play an importance rule. These strategies namely as open loop, closed loop and feedback. The different between open loop and close loop strategies is only on reaction effects. Due to this, it is expected that open-loop differential games will generate same results such as static competition. In the other hand, the concept of equilibrium feedback strategy is found to be more natural and interesting in the present problems because the firms cannot deviate separately from equilibrium strategy. Therefore, this research work attempts to developed and solve models for differential oligopolistic game theory, which include sticky prices and advertising, Research and Development (R&D) process, as well as capital accumulation and subsidy parameters. In this model the authors solved the dynamics open market by enhancing the three different strategies namely open loop, close loop andfeedback for homogeneous or differentiated products using Hamilton-Jacobian-Bellman (HJB) method.The main findings of this studyshows that advertising initiatives employed in a setting based on the open loop, close loop andfeedback strategy increase the product differentiation, price stickiness, and promotional efficiency. On the hand the advertising effort efficiencyin the feedback strategy shows in opposite way.Feedback and close-loop equilibriums can separately be differentiated more efficient compared to open-loop competition in the event of high R&D productivity or close product substitutes. The scenario of feedback competition also consistently shows that social welfare (SW) and consumer surplus (CS) is higher than in close loop and open loop strategy. This research proposed the usage of an engineering applicationto solvea very challenging economic problem pertaining to the capital accumulation of electrical market. For instance, the author has implemented this model for finding the effects of subsidy due to deregulating of electricity markets. It can be observed that by using this model, the social welfare is increase with the increasing of subsidy effort. However, the number of power plants that manage to survive over time decreases. In other words, social welfare increases due to an increase in consumer surplus, while additional power plants would initiate an increase in capital or output, leading to a decrease in electricity price.